Energy economics CO₂ emissions in China - Wei, Yiming; SpringerLink (Online service). (Berlin London Springer, 2011)
"Energy Economics: CO2 Emissions in China" presents a collection of the researches on China's CO2 emissions as studied by the Center for Energy & Environmental Policy Research (CEEP). Based on the analysis of factors related to global climate change and CO2 emissions, it discusses China's CO2 emissions originating from various sectors, diverse impact factors, as well as proposed policies for reducing carbon emissions. Featuring empirical research and policy analysis on focused and critical issues involving different stages of CO2 emissions in China, the book provides scientific supports for researchers and policy makers in dealing with global climate change.
Energy use and carbon dioxide emissions -- Analysis of energy consumption and CO2 emissions in China -- Study on impact factors of CO2 emissions under different economic development levels -- Evolution characteristics of CO2 emissions in carbon-intensive sectors in China -- Impacts of household consumption and export trade on CO2 emissions -- Study on regional CO2 emissions change in China -- CO2 emissions abatement technology and impact analysis -- Simulations of CO2 mitigation policies -- International carbon market and its impacts on CO2 emission abatement -- Outlook of CO2 abatement in China.
Electronic reproduction.
Keywords: Energy policy -- Environmental aspects -- China; Carbon dioxide -- Environmental aspects; Greenhouse effect, Atmospheric -- Economic aspects; Pollution -- China; Electronic books